2021
DOI: 10.1371/journal.pone.0256977
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of deterioration of respiratory status when steroids precede antiviral drugs in patients with COVID-19 pneumonia: A retrospective study

Abstract: Introduction Coronavirus disease (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2. Although most patients with COVID-19 develop asymptomatic or mild disease, some patients develop severe disease. The effectiveness of various therapeutic agents, including antiviral drugs, steroids, and anti-inflammatories for COVID-19, have been being confirmed. The effect of administering steroids in early disease is unclear. This study therefore aimed to evaluate the effectiveness and risk of exacerbati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
3
6
0
Order By: Relevance
“…19 A previous study reported that the administration of steroids prior to antiviral therapy soon after symptom onset could result in poor outcomes. 12 Although steroids therapy with or without antiviral drug might influence the rebound phenomenon, the ratio of antiviral use was similar between the two groups in the present study. Likewise, some studies reported that the combination of steroids plus anti-IL-6 antibody or other immunosuppressants showed better outcomes than steroids monotherapy, 3 6 and the use of other immunosuppressants in this study did not show any difference between the two groups.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…19 A previous study reported that the administration of steroids prior to antiviral therapy soon after symptom onset could result in poor outcomes. 12 Although steroids therapy with or without antiviral drug might influence the rebound phenomenon, the ratio of antiviral use was similar between the two groups in the present study. Likewise, some studies reported that the combination of steroids plus anti-IL-6 antibody or other immunosuppressants showed better outcomes than steroids monotherapy, 3 6 and the use of other immunosuppressants in this study did not show any difference between the two groups.…”
Section: Discussionsupporting
confidence: 50%
“… 10 11 This suggested that the duration or dosage of steroids therapy could be insufficient for some cases. Shionoya et al 12 reported that the administration of steroids prior to antiviral drugs soon after symptom onset leads to a poor outcome but whether administrating steroid with or without antiviral drugs is associated with the rebound phenomenon is unclear. Many clinical parameters, such as age, coexisting diseases, lymphocyte count, D-dimer and lactate dehydrogenase (LDH), have been reported as predictors of COVID-19 progression since the COVID-19 pandemic began.…”
Section: Introductionmentioning
confidence: 99%
“…This can be at least partly explained by the characteristics of the patients who received steroids, who presented a higher prevalence of dismal prognostic factors such as hypertension, obesity or diabetes among others and higher levels of biomarkers associated with poor outcome in COVID-19 (D-dimer, C-RP). Nevertheless, we cannot exclude that in some cases steroid could have been administered too early, during the viral phase of the disease, which has been associated with worse outcomes [15,16]. In addition, corticosteroids are not exempt of adverse effects, in particular when given at high-dose, and in patients without severe involvement the risk-benefit ratio may not be favorable.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, in these trials, administration of colchicine in association to standard therapy did not result in significant difference on several composite endpoints, including intubation for mechanical ventilation or 28-day mortality ( 19 ), admission and length of stay in ICU, death rate and cause of mortality ( 24 ), change in WHO 7-point scale ( 26 ), and 28-days all-cause mortality ( 27 ). As a consequence, current guidelines and a recent Cochrane meta-analysis do not support the use of colchicine in hospitalized patients with moderate to severe COVID-19 ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 98%